Orlistat is a fatty acid synthase (FASN) inhibitor caused the modulation of AMPK and lipogenesis signaling axis in PC3 prostate cancer cells but not in PNT1A prostate epithelial cells - Nebiler, Esra; Adacan, Kaan; Çoker Gürkan, Ajda; Palavan Ünsan, Narçın; ARISAN, ELİF DAMLA; YERLİKAYA, PINAR OBAKAN (My University, 2017)
Prostate cancer is one the leading cancer type after lung cancer among male. Obesity is one of the known risk factor for developing highly aggressive and metastatic prostate cancer, which is an obstacle in cancer therapy. For these particular reasons, drugs are used in the therapy of obesity is suggested with their antitumoral effect, whether blocking adipogenesis and lipogenesis pathways or not. Orlistat inhibits fatty acid synthase (FASN), a large multifunctional enzyme, is responsible for de novo synthesis of long chain fatty acids. FASN activity is confirmed in the most of the xenograft models of prostate cancer cells. In this study we utilized PC3 cells, medium FASN expression profile compared to DU145 and LNCaP cells, and PNT1A prostate epithelial cells to evaluate the molecular targets of orlistat in adenosin mono phosphate kinase (AMPKa) and lipogenesis signaling axis. We demonstrated that orlistat inhibited cell proliferation and led to cell viability decrease in PC3 prostate cancer cells but not in PNT1A prostate epithelial cells. The activation of AMPKa was observed in both cell lines, which led to inhibition of protein translation through dephosphorylating mTOR at ser2448 and phosphorylating mTOR at ser2481 after treatment with Orlistat at 15 µM and 20 µM concentrations for 24h. Concomitantly, orlistat induced autophagy via phosphorylation of ULK1 at ser555. The modulation of AcetylCoA carboxylase (ACC), which regulates biosynthesis and oxidation of fatty acids was observed following orlistat treatment. However, AMPK phosphorylates ACC at ser79 and inhibits its activity. These findings suggest that orlistat altered AMPKrelated a number of critical pathways to exert its antitumor activity in prostate cancer cells. However, AMPK is a metabolic stress regulator protects epithelial normal cells against orlistat treatment. Thereby, it is crucial to have deep understanding about the role of AMPK in prostate cancer cells.